Afrika Remix : Zeitgenossische Kunst Eines Kontinents - Njami, Simon (Museum Kunst Palast; Hatje Cantz Verlag, 2004)
Exhibition catalog. Exhibition venues: Hayward Gallery, London; Centre Georges Pompidou, Paris; Mori Art Museum, Tokyo. Contributors: Simon Njami, David Elliott, Jean-Huert Martin, Marie-Laure Bernadac, John Picton, Jean-Loup Amselle, Jean-Hubert Martin, Francois Bensignor, Manthia Diawara, Bernard Muller, Hudita Nura Mustafa, Clementine Deliss, Yukiya Kawaguchi, Marie-Christine Eyene, Charlotte Boudon, Thomas Boutoux, Cedric Vincent.
German
Keywords: Contemporary Art; N4390-5098 Exhibitions; Africa